Towards the Highly Efficient Synthesis and Selective Methylation of C(sp3)‐Bridged [6]Cycloparaphenylenes from Fluoren[3]arenes. (6th May 2021) - Du, Xu‐Sheng; Zhang, Da‐Wei; Guo, Yan; Li, Jing; Han, Ying; Chen, Chuan‐Feng
Abstract: An approach to the highly efficient synthesis of C(sp3)‐bridged [6]cycloparaphenylenes (C[6]CPPs ) from fluoren[3]arenes (F[3]As ) was developed. Consequently, F[3]As as a new kind of macrocyclic arenes were synthesized. Followed by the demethylation, triflation and intramolecular aryl–aryl coupling reactions, C[6]CPPs were then conveniently obtained. Interestingly, C[6]CPPs could be selectively methylated to produce their fully outer‐methyl‐substituted derivatives. The crystal structures showed the hydroxyl‐substituted F[3]As had bowl‐shaped conformations, and the C[6]CPPs exhibited rigid belt‐shaped structures with deep cavities. Moreover, C[6]CPPs exhibited high HOMO energies and narrow energy gaps. An unclosed belt was further obtained, and it not only showed a similar narrow energy gap to those of the aromatic belts, but also displayed strong fluorescence property, which can play a vital role in the design and synthesis of new aromatic belts. Abstract : Starting from fluoren[3]arenes, a new kind of easily available macrocyclic arenes, a powerful approach to the highly efficient synthesis of C(sp 3 )‐bridged [6]cycloparaphenylenes (C[6]CPPs ) with aesthetic conjugated belt structures was developed. Moreover, the bridged methylene of C[6]CPPs could be selectively methylated to produce their fully outer‐methyl‐substituted derivatives in ≥96 % yields.